Immunogenicity and protective potential of Bordetella pertussis biofilm and its associated antigens in a murine model - Dorji, Dorji; Graham, Ross; Singh, Abhishek; Ramsay, Joshua; Price, Patricia; Lee, Silvia (Academic Press, 2019)
© 2019 Elsevier Inc. The resurgence of whooping cough reflects novel genetic variants of Bordetella pertussis and inadequate protection conferred by current acellular vaccines (aP). Biofilm is a source of novel vaccine candidates, including membrane protein assembly factor (BamB) and lipopolysaccharide assembly protein (LptD). Responses of BALB/c mice to candidate vaccines included IFN-γ and IL-17a production by spleen and lymph node cells, and serum IgG1 and IgG2a reactive with whole bacteria or aP. Protection was determined using bacterial cultured from lungs of vaccinated mice challenged with virulent B. pertussis. Mice vaccinated with biofilm produced efficient IFN-γ responses and more IL-17a and IgG2a than mice vaccinated with planktonic cells, aP or adjuvant alone. Vaccination with aP produced abundant IgG1 with little IgG2a. Mice vaccinated with aP plus BamB and LptD retained lower bacterial loads than mice vaccinated with aP alone. Whooping cough vaccines formulated with biofilm antigens, including BamB and LptD, may have clinical value.